Relationships between volatile organic compounds with an emphasis on terpene compounds and genetic matrix in inoculated and non-inoculated winter wheat cultivars. Issue 10 (26th November 2019) - Buśko, M.; Góral, T.; Boczkowska, M.; Perkowski, J.
ABSTRACT: In the present study, we focus on the analysis of the volatile organic compound (VOC) contents in the grain of a representative set of winter wheat cultivars grown in Central Europe. The cultivars were grown in control conditions or were inoculated with the fungus Fusarium culmorum . In the analysed samples, hydrocarbons, alcohols, aldehydes and ketones, aromatics, terpenes and others were found. Among them, results for terpenes seem particularly important. The discriminant analysis allowed complete separation of the quality groups of wheat based on VOCs. Simultaneously, a genetic matrix was created based on the genetic distance between the wheat cultivars and the Mantel test was used to compare it with the VOC matrix. The analysis revealed relationships between the genetic matrix and the overall VOCs, as well as terpenes. The obtained results indicate a significant relationship between microorganisms that exist in the environment, genetic features of plants and VOCs formed in the grain.